PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN DI ALFAMART AKSES GALAKSI, BEKASI SELATAN - Vika Aninda; Harry Indratjahyo (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
This research is aimed to analyze in the corelation between the price fluctuation and the service quality through the customer satisfaction of Alfamart Akses Galaksi. The data collecting was conducted within the questioner method towards 100 Alfamart Akses Galaksi’s customers, and being analyzed by using SPSS Version 22. The data given was being tested in consists of validity with the Factor Analysis, and Reliability Test by using Alpha Cronbach. The classic assumption testing and double linier regretion, is to verify and prove this research’s hypothesis. The result shows that there has been a positive corelation between the price fluctuation and service quality through the customers’ satisfaction. On the result of simultanious regretion test, it was found ot that F counted> F Ttable > and significant <0,05. While for the double corelation (R) and determination coeficience (R2), determined that R = 0,872 (near to 1) dan R2 = 0,760 within 76% and the rest 24% is impacted by other variables which is not included in this research. (T test), it was found out that T counted > T table and significance < 0,05. Total contribution of the price through the customers’ satisfaction based on the table above is R2 (R square) sebesar 0,581 or 58,1% and the rest 41,9% impacted by other variables which is not included in this research. Meanwhile for the service quality variable towards the customers’ satisfaction on the partial testing (T test), resulted that T counted > T table and significance < 0,05. Total contribution of the service quality through the customers’ satisfaction based on the table above resulted that R2 (R square) is 0,734 or 73,4% and the rest 26,6% is impacted by other variables which is not included in this research.